HUBUNGAN MOTIVASI IQ DAN KEPERCAYAAN DIRI TERHADAP HASIL BELAJAR PENJAS - Irvan Albarkah Hilmana (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2022)
This study aims to find out whether there is a relationship between IQ motivation and student confidence alone and together the learning outcomes of students of class VIII junior high school Al amah Cimanggung. The research method used is Quantitative Descriptive, a population of 125 students from all students of class VIII al amah Cimanggung junior high school. Data taken for free variables and bound them using questionnaires. The data analysis techniques used are descriptive statistics, correlations and regressions at a significance level of 5%. The results of the study of class VIII Junior High School Al amah Cimanggung found (1) a positive and significant relationship between motivation to learning outcomes is indicated by a coefficient of r of 0.572, and the significance of the relationship of variable X1 with variable Y can be seen the value of t calculated by 31,464 > with t table (n-2) of 2,048, and the large increase in motivation every 1 point then the learning outcome increases by 0.298.. (2) The existence of a positive and significant relationship between IQ and student learning achievement is indicated by a coefficient of r of 0.515 and the significance of the relationship of variable X2 with variable Y can be seen the value of t calculated by 33,788 > with t table (n-2) of 2.048, and the magnitude of the increase in IQ every 1 point then the learning outcome of the generator increased by 0.219. (3) The existence of a positive and significant relationship between student confidence and student learning outcomes is indicated by a coefficient r of 0.552, and the significance of the relationship of variable X3 with variable Y can be seen the value of t calculated by 34,952 > with t table (n-2) of 2,028, and the large increase in confidence every 1 point then the learning outcome increases by 0.221.(4) The existence of a positive and significant relationship between student motivation and IQ with student learning outcomes is indicated by a double correlation coefficient of r_y12 of 0.692 and the significance of the relationship of variables X1 and X2 with variable Y can be seen the value of F calculated by 27,368 > with F table (n-2) of 2.98, and a large increase in motivation and IQ every 1 point then the learning results of the generator increased by 0.248 and 0.171.(5) The existence of a positive and significant relationship between student motivation and confidence with learning outcomes is indicated by a double coefficient of r_y12 of 0.533 and the significance of the variable relationship X1 and X3 with variable Y can be seen the value of F calculated by 15,426 > with F table (n-2) of 2.98, and a large increase in motivation and confidence every 1 point then the learning results of the generator increased by 0.253 and 0.185. (6) The existence of a positive and significant relationship between IQ and student confidence with learning outcomes is indicated by a double coefficient of r_y12 of 0.454 and the significance of the relationship of variables X2 and X3 with variable Y can be seen the value of F calculated by 11,204 > with F table (n-2) of 2.98, and a large increase in IQ and confidence every 1 point then the learning results of the generator increased by 0.170 and 0.180. (7) The existence of a positive and significant relationship between motivation, IQ and student confidence with learning outcomes is indicated by a double coefficient of r_y12 of 0.620 and the significance of variable relationships X1, X2 and X3 with variable Y can be seen the value of F calculated by 14,143 > with F table (n-2) of 2.98, and great increase in motivation, IQ and confidence every 1 point then the learning outcome increases by 0.221, 0.133 and 0.158.